Regional embeddedness of information- and communication technology enterprises: A case-study in the TechnologieRegion karlsruhe - Matuschewski, Anke; Zoche, Peter (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
Information- and communication technology (ICT) enterprises act in dynamic, international markets. However, the existence of region ICT-clusters proposes that firms are regionally embedded and demand specific conditions. The paper presents results from a case-study in the ‘TechnologieRegion Karlsruhe’. The firms show a considerable degree of regional co-operation, but young and small enterprises tend to be not sufficiently integrated within regional networks. The study also shows that ICT-firms do not differ significantly from other “traditional” sectors regarding co-operation.
Keywords: Article